2011
DOI: 10.2320/matertrans.m2011146
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Walled Carbon Nanotube-Aluminum Matrix Composites Prepared by Combination of Hetero-Agglomeration Method, Spark Plasma Sintering and Hot Extrusion

Abstract: Multi-walled carbon nanotubes (MWCNTs) with outstanding mechanical properties are considered as an ultimate reinforcement for conventional metals such as aluminum (Al), though they require uniform dispersion and intimate contacts with the host metal matrix. However, bundled structure of chemically stable, pristine MWCNTs has been the main challenge to achieving the expected structural reinforcement. In addition, the sole contribution of MWCNTs in strengthening the metal matrix has not been recognized yet, due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 23 publications
6
27
0
2
Order By: Relevance
“…It is essential to find a compromise between these two factors. The techniques described in the literature, which confer the best results of CNT dispersion, are comprise of mechanical processes [4,5] and the chemical and physical modifications of the CNTs (CNT functionalization) [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to find a compromise between these two factors. The techniques described in the literature, which confer the best results of CNT dispersion, are comprise of mechanical processes [4,5] and the chemical and physical modifications of the CNTs (CNT functionalization) [6].…”
Section: Introductionmentioning
confidence: 99%
“…ose processing routes include powder metallurgy [6][7][8][9][10][11][12][13][14], high-energy ball milling [15,16], friction stir processing [17], spark plasma sintering [18], plasma spraying [19][20][21], and more recently laser sintering [22]. However, the obtained results are still not completely satisfactory, because the extreme processing conditions, either thermal or impact, can damage the CNT structure and cause a detrimental effect on the final mechanical properties of the composite.…”
Section: Introductionmentioning
confidence: 80%
“…A recent study by Rashad et al [146] showed that the formed intermetallics in MWNTs-dispersed Mg-3Al-1Zn alloys are refined with the CNTs inclusion. Figure 23 indicates the schematic demonstration of Mg 17 Al 12 generation at the interface of Mg-3Al-1Zn/MWNTs composite, where the coarse particles of Mg 17 Al 12 can be refined through the incorporation of MWNTs into the matrix. Figure 22.…”
Section: (C) Cnt-reinforced Mg Matrix Nanocompositesmentioning
confidence: 99%
“…To overcome this challenge, a broad spectrum of dispersion methods is developed. Among these techniques, the mechanical methods [15], surface treatment [16], and chemical methods [17] are the most conventional. Each of these techniques has their own advantages and disadvantages, being discussed in the next sections.…”
Section: Introductionmentioning
confidence: 99%